Ukrainian Ophthalmology in Names: Dr. Mykhailo Kos (1863-1930) (Ukrainian Journal of Ophthalmology, 2025)
This paper highlights the complex personality of Mykhailo Kos, a Ukrainian military doctor, ophthalmologist, and an outstanding public figure. The authors described his life and contribution to science as well as articles in periodicals. His works on ophthalmology and articles directed at providing eye health information to the public were subjected to analysis.Mykhailo Kos’ legacy is wide and multifaceted, and his works require close attention of historians and ophthalmologists. The doctor’s publications were directed primarily both at burning academic ophthalmological issues of that time and at providing health information and education to the Ukrainian public, with an emphasis on prevention of eye disorders.In addition, he published biographical works on a number of famous figures in the field of medicine and, what is especially interesting, in the field of humanitarian law. The multifaceted nature of Mykhailo Kos came out when he co-established and contributed to the development of the Ukrainian Medical Society which included Ukrainian doctors from eastern Galicia. His military career is also worth the reader's attention. Although for most this career involved serving in the Austrian army, his patriotic spirit called him to the development of and service for the Ukrainian state in the early 20th century, in the years of the Ukrainian Liberation Struggle at western Ukraine.Another proof of the estimation of his contribution to science we find in electing Mykhailo Kos a Member of the Shevchenko Science Society.His personal field journals and notebooks written during World War I are of particular interest.
Keywords: ophthalmologist; military doctor; medical practice; eye disease; malingering; spectacles; cataract; strabismus; ocular defects